2007
DOI: 10.1016/j.ajodo.2005.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cariogenic streptococci on incisor brackets detected by polymerase chain reaction

Abstract: Introduction: Streptococcus mutans and Streptococcus sobrinus are the main causative organisms for enamel demineralization during orthodontic treatment. In this study, we analyzed the prevalence of cariogenic streptococci adhering to incisor brackets. Methods: Four incisor brackets from both the maxilla and the mandible were collected from 80 patients at debonding, immediately after the visible plaque index and the gingival bleeding index were measured from the incisors. The genomic DNA of adhered cariogenic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
12

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 21 publications
(31 reference statements)
1
36
0
12
Order By: Relevance
“…The subsequent growth of these initially adherent bacteria that have been removed incompletely by tooth brushing may eventually lead to the formation of a pathogenic oral biofilm. [8][9][10][11] Organic acids produced by the adherent bacteria can cause enamel demineralization around a bracket, which can cause deterioration of the orthodontic treatment outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The subsequent growth of these initially adherent bacteria that have been removed incompletely by tooth brushing may eventually lead to the formation of a pathogenic oral biofilm. [8][9][10][11] Organic acids produced by the adherent bacteria can cause enamel demineralization around a bracket, which can cause deterioration of the orthodontic treatment outcome.…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with those of Chang et al 24 and ulukapi et al 25 .isolation of cariogenic microflora has been based on laboratory procedures (colonial morphology grown, biochemical and immunologic tests), which can be inaccurate. PCr is a sensitive and specific method that uses specific dnA fractions for detection of microorganisms 26 . results from this study indicated a slight, statistically nonsignificant increase in cariogenic microflora during the t1-t2 period.…”
Section: Resultsmentioning
confidence: 99%
“…1 Prevalensi karies yang tinggi 90% terjadi pada anak-anak dan terutama anak pemakai ortodonti cekat dimana terjadi aktifitas mikroorganisme yang menyebabkan enamel demineralisasi yang secara klinis terlihat sebagai white spot lesion disekitar brackets. 2,3 Berbagai mekanisme dapat digunakan dalam mencegah karies, antara lain dengan mengubah kebiasaan pasien dalam mengkonsumsi makanan yang berkarbohidrat tinggi, meningkatkan kebersihan mulut dan menggunakan obat kumur antiseptik, namun obat kumur tidak direkomendasikan untuk anak karena mempunyai efek samping jika digunakan dalam jangka panjang dan pada kenyataannya rasa obat kumur tidak disukai sebagian besar anak-anak.…”
Section: Kata Kunci: Probiotik Yoghurt Anak Streptococcus Mutans Bunclassified